Effectiveness of Spiritual Care in Reducing Death Anxiety Among Patients Receiving Palliative Care: An Integrative Literature Review - Dian Kusuma Dewi; Wantonoro Wantonoro; Islamiyatur Rokhmah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Death anxiety is a common psychological and existential concern among patients with chronic, terminal, and palliative illnesses, adversely affecting emotional well-being, quality of life, and coping ability. Spiritual care has been increasingly recognized as an essential component of holistic palliative care; however, evidence regarding its effectiveness in reducing death anxiety remains fragmented. Objective: This integrative literature review aimed to synthesize current evidence on the effectiveness of spiritual care in reducing death anxiety among patients receiving palliative care. Methods: An integrative literature review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines. Six electronic databases (PubMed, ScienceDirect, SAGE Journals, ProQuest, SpringerLink, and Wiley Online Library) were searched for English-language studies published between 2021 and 2026. Eligible studies included randomized controlled trials, quasi-experimental studies, and analytical cross-sectional studies involving adults with chronic, terminal, or palliative illnesses. Methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools, and findings were synthesized narratively using thematic analysis. Results: Eight studies met the eligibility criteria, comprising two randomized controlled trials, one quasi-experimental study, and five analytical cross-sectional studies. Three overarching themes emerged: (1) spirituality as a protective factor against death anxiety, (2) the effectiveness of spirituality-based interventions in reducing death anxiety, and (3) mechanisms through which spiritual care enhances psychological adaptation. Higher levels of spiritual well-being, meaning in life, and fulfillment of spiritual care needs were consistently associated with lower death anxiety. Structured interventions, including spiritual counseling, nurse-led spiritual care, and spirituality-oriented palliative care, significantly reduced death anxiety while improving resilience, psychological well-being, and quality of life. Conclusion: Spiritual care is an effective non-pharmacological intervention for reducing death anxiety and supporting psychological adaptation among patients receiving palliative care. Integrating evidence-based spiritual care into routine nursing practice may enhance holistic, person-centered care. Further multicenter randomized controlled trials using standardized interventions are needed to strengthen the evidence base